Systematic analyses of radiocarbon ages of coexisting planktonic foraminifera - Lippold, Jörg; Gottschalk, Julia; Lynch-Stieglitz, Jean; Schmidt, Matthew W.; Szidat, Sönke; Bahr, André (Radiocarbon, 2023)
We compare radiocarbon (14C) ages of coexisting planktonic foraminifera species from sediment cores VM12-107 and KNR166-2-26JPC from the Equatorial Atlantic Ocean for three time periods (Holocene, Heinrich Stadial 1, last glacial maximum). We find a maximum inter-species difference of 1200 14C yr. On average, the 14C ages deviate by ∼300 yr between Globigerinoides ruber and other species. In most cases, this exceeds the analytical uncertainty range of the measurements and thus renders the choice of species for generating age models as important as sample weight. While modern stratified water-column profiles imply an increase in 14C ages with water depth, we observe an expected parallel increase of 14C ages and δ18O only at VM12-107. The mismatch between 14C ages and δ18O at KNR166-2-26JPC likely results from the effects of bioturbation and the hydrographic setting. The largest difference in 14C ages between mixed-layer versus thermocline-calcifying planktonic foraminifera are observed during Heinrich Stadial 1 despite a decrease in upper-ocean stratification at that time. This difference is likely the result of inconsistent increases in 14C reservoir ages during times of reduced overturning circulation masking the potential of 14C ages of coexisting planktonic foraminifera to reflect the density stratification of the water column.